A simple method for well-defined and clean all-SiC nano-ripples in ambient air. (July 2016) - Ma, Yuncan; Khuat, Vanthanh; Pan, An
Abstract: Well-defined and clean all-SiC nano-ripples with a period of about 150 nm are produced via the combination of 800-nm femtosecond laser irradiation and chemical selective etching with mixture solution of 65 wt% HNO3 acid (20 mL) and 40 wt% HF acid (20 mL). The incorporation mechanism of oxygen (O) species into the laser induced obscured nano-ripples is attributed to femtosecond laser induced trapping effect of dangling bonds, while that of chemical etching induced well-defined and clean nano-ripples is assigned to chemical reactions between mixture acid solution and amorphous silicon carbide (SiC) or silicon oxide (SiO2 ). Results from EDX analysis show that the incorporated foreign O species (atomic percentages of 9.39%) was eliminated effectively via chemical etching, while the atomic percentages of silicon (Si) and carbon (C) were about 47.82% and 52.18% respectively, which were similar to those of original SiC material. And the influences of laser irradiation parameters on the nano-ripples are also discussed. Graphical abstract: Highlights: A simple and practical method, using the combination of 800-nm femtosecond laser irradiation and chemical selective etching, for the fabrication of well-defined and clean all-SiC nano-ripples, has been proposed. Incorporation mechanism of oxygen species into the obscured nano-ripples was attributed to the femtosecond laser induced trapping effect of dangling bonds. Formation mechanism of the well-defined and clean nano-ripples was assigned to the chemical reactions between mixture acid solution and amorphous silicon carbide or silicon oxide. The influences of laser irradiation parameters on the nano-ripples were systematically discussed.